SYNTHESIS AND MODIFICATION OF CUPPER 1,4 BENZENEDICARBOXYLATE AS GOOD CANDIDATE FOR POST-COMBUSTION GAS ADSORBENT - Muttaqin Muttaqin; Rehan Rizkyta Peranginangin (JURNAL TEKNOLOGIA, 2021)
The use of fossil-based fuels has serious implications on the environmental issues because it will increase the emission of carbon dioxide (CO2) gas which will contribute on the global warming. Therefore, it is necessary to develop technologies, methods or materials that can capture or storage CO2 levels in the air. One of the materials that can be used as a CO2 gas absorbent is a material called a metal organic framework (MOF). MOF with a Cu metal core and a ligand, 1,4-benzene dicarboxylic acid will form a porous material with a triclinic crystal structure. This material is called cupper-benzene dicarboxylate (CuBDC). This study aims to synthesize and modify CuBDC with ethylenediamine compound. The characterization results show that CuBDC and CuBDC-modification have been confirmed based on the analysis of Fourier transform infrared spectrophotometer (FTIR) and X-ray diffraction (XRD). The synthesized MOFs have good thermal resistance where the main-frame structure can withstand temperatures up to 300's C. Modified-CuBDC has a much larger surface area, pore diameter and pore volume compared to CuBDC so that modified-CuBDC has the potential to be used as an absorbent material for CO2 gas produced by combustion by the power generation industry or other industries.